(untitled) (REMUNOM, 2025)
This study examines the journalistic discourse present in political reports published by Jornal do Commercio and Folha de S. Paulo, focusing on both state and national levels. The main objective is to evaluate whether these media outlets serve as legitimate spaces for disseminating information and fostering diverse perspectives, both of which are essential for public debate. The research operates on the premise that the quality of journalistic coverage is deeply tied to journalists’ autonomy from external pressures, whether bureaucratic or market-driven. This autonomy is vital to ensuring a critical and accurate symbolic representation of reality, which is fundamental for the full exercise of political citizenship. The methodology is grounded in a theoretical framework that incorporates Matt Carlson’s (2017) theory of journalistic authority, the analyses of Edward Herman (2016) and Warren Breed (2016), and Jürgen Habermas’s (1997, 2004) theory of the public sphere, which provides insights into how media can function as a platform for public debate and the formation of public opinion.